2018
DOI: 10.3390/ijerph15091944
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipid Profile and Its Association with Diabetes and Prediabetes in a Rural Bangladeshi Population

Abstract: Dyslipidemia is commonly associated with diabetes (T2DM). This has been demonstrated for the Caucasian population, but few data are available for Asian Indians. The paper aims to investigate serum lipids (separately or in combination) and their association with glucose intolerance status (T2DM and prediabetes) in a rural Bangladeshi population. A sample of 2293 adults (≥20 years) were included in a community based cross-sectional survey in 2009. Anthropometric measures, blood pressure, blood glucose (fasting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
84
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 56 publications
22
84
2
1
Order By: Relevance
“…In addition, these combined metabolic disorders like hypertension and hyperlipidemia may lead to cardio-cerebrovascular diseases and stroke, which may eventually lead to death (Sun et al, 2014). One study revealed that Total cholesterol (TC), raised triglycerides (TGs) and low HDL-cholesterol (HDL-c) were increased significantly in type-2 DM patients (Bhowmik et al, 2018). HDL-c showed an inverse association with body mass index (BMI); but LDL-c, TC and TGs were positively correlated with BMI (Omotoye et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these combined metabolic disorders like hypertension and hyperlipidemia may lead to cardio-cerebrovascular diseases and stroke, which may eventually lead to death (Sun et al, 2014). One study revealed that Total cholesterol (TC), raised triglycerides (TGs) and low HDL-cholesterol (HDL-c) were increased significantly in type-2 DM patients (Bhowmik et al, 2018). HDL-c showed an inverse association with body mass index (BMI); but LDL-c, TC and TGs were positively correlated with BMI (Omotoye et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple set of studies have been conducted to establish the importance of improving dyslipidemia in relation to diabetes [29,30] and so effects of metformin on the same [31]. Our data too, revealed the beneficial effects of metformin on serum cholesterol, TG and HDL but in the setting of PCOS.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, high levels of TG in combination with low levels of HDL showed the highest association with T2DM and PD. The levels of high CHOL, high TG, and low HDL were more elevated among subjects with T2DM and PD (13).…”
Section: Resultsmentioning
confidence: 87%
“…For instance, a meta-analytic review demonstrated that lipid pro le disorders signi cantly associated with T2DM (12). A community based cross-sectional survey showed a strong association between serum lipid pro le with T2DM and PD (13).…”
Section: Introductionmentioning
confidence: 99%